(untitled) - Lee, Stephen (Harlow, Eng., 2001)
This edition includes a substantial amount of new material including a comprehensive section on medicine in prehistoric times as well as plenty of new sources providing extra exam practice.
Keywords: Public health,Medical care,Medicine; History